Cell-Mediated Immunity in Humans During Viral Infection: Dermal Hypersensitivity and In Vitro Lymphocyte Proliferation During Mild Viral Respiratory Infections - Kauffman, Carol A. (1974)
In vitro lymphocyte proliferation in response to phytohemagglutinin and streptokinase-streptodornase and delayed dermal hypersensitivity to several antigens were assessed in patients with mild viral upper respiratory infections. The response to phytohemagglutinin in 18 patients was not diminished during the viral infection. Deoxyribonucleic acid synthesis induced by streptokinase-streptodornase remained unaffected by the viral illness in five patients, and skin test reactivity was not depressed during the viral infection. Thus, it appeared that localized viral upper respiratory infections were not associated with suppression of systemic cell-mediated immunity.